2015
DOI: 10.1182/blood-2015-03-635326
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of MCL patients treated with single-agent ibrutinib: updated safety and efficacy results

Abstract: Key Points• Ibrutinib demonstrates durable responses and sustained single-agent activity in relapsed or refractory MCL at median 26.7-month follow-up.• Ibrutinib shows a favorable benefit-risk profile over time, with a manageable safety profile.Ibrutinib, an oral inhibitor of Bruton tyrosine kinase, is approved for patients with mantle cell lymphoma (MCL) who have received one prior therapy. We report the updated safety and efficacy results from the multicenter, open-label phase 2 registration trial of ibrutin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
308
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(341 citation statements)
references
References 12 publications
25
308
2
6
Order By: Relevance
“…The BTK inhibitor ibrutinib, with or without weekly dex, demonstrated promising activity and was well tolerated in this heavily pre‐treated RRMM population with a median of 4 prior lines of therapy, including 74% of patients who had disease that was refractory to their most recent therapy. The AEs reported in this trial were consistent with the safety profile of ibrutinib observed across other B‐cell malignancies (Burger et al , 2015; Wang et al , 2015; Castillo et al , 2016; Falchi et al , 2016). The majority of AEs reported were grades 1–2 and were managed with supportive care.…”
Section: Discussionsupporting
confidence: 84%
“…The BTK inhibitor ibrutinib, with or without weekly dex, demonstrated promising activity and was well tolerated in this heavily pre‐treated RRMM population with a median of 4 prior lines of therapy, including 74% of patients who had disease that was refractory to their most recent therapy. The AEs reported in this trial were consistent with the safety profile of ibrutinib observed across other B‐cell malignancies (Burger et al , 2015; Wang et al , 2015; Castillo et al , 2016; Falchi et al , 2016). The majority of AEs reported were grades 1–2 and were managed with supportive care.…”
Section: Discussionsupporting
confidence: 84%
“…Such constructs have a long blood retention time compared to blinatumomab and could be applied more conveniently. Despite improved FcγR affinity, this type of antibodies show only few side effects when applied in patients, 9 , 15 and, importantly, side effects of T-cell activation such as CRS and encephalopathy may be avoided. Despite such expected advantages compared to blinatumomab or CAR T cells, it remains to be determined whether Fc engineered antibodies will be equally efficient in the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…An important approach for that purpose is the use of immunotherapies, and therapy with Fc engineered CD19 antibodies may represent a powerful option with few side effects. 8 , 9 , 15 , 16 …”
Section: Cd19 Targeting With Fc Engineered Antibodies Optimized For Ementioning
confidence: 99%
See 1 more Smart Citation
“…Temsirolimus versus single‐agent IC (primarily, gemcitabine and fludarabine) showed consistently longer PFS across sex, performance status, disease stage at diagnosis, bone marrow involvement and number of prior regimens in exploratory subgroup analyses of a phase III trial (Hess et al , 2009) and in a recent retrospective analysis, across MIPI risk categories (Hess et al , 2015). Subgroup analyses of a single‐arm phase II trial of ibrutinib in 111 patients with relapsed/refractory MCL found similar ORRs, irrespective of multiple baseline factors, including tumour bulk (≥5 and ≥10 cm cut‐offs), ≥2 prior treatment regimens and refractory disease (less than partial response to last prior therapy) (Wang et al , 2015). More recently, an open‐label phase III study showed that ibrutinib was superior to temsirolimus with regard to improvements in PFS overall and when broken down by subgroups (Dreyling et al , 2016).…”
Section: Discussionmentioning
confidence: 97%